2022
DOI: 10.3390/math10111948
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing Policies with an Allowable Discount for Perishable Items under Time-Dependent Sales Price and Trade Credit

Abstract: Trade credit is generally used by businesses to obtain external funds. This article demonstrates an inventory system from the retailer’s point of view in which (1) the influence of trade credit on expanding small businesses and their consumers is the focus of this research, and (2) the retailer’s on-hand inventory follows the non-instantaneous deterioration. (3) To maximize profit, the demand is disclosed, which is based on not just the sales price, but also on cumulative demand, which indicates saturation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The demand is affected by the combined effect of selling price and stock age, and the deterioration rate is time-varying. Additional articles related to this topic from the last decade can be found in the works of various authors, including Li et al [36], Chung et al [37], Jani et al [38], and others. A comparison of the present paper with the relevant literature is provided in Table 1 to help the readers understand the contributions of our model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand is affected by the combined effect of selling price and stock age, and the deterioration rate is time-varying. Additional articles related to this topic from the last decade can be found in the works of various authors, including Li et al [36], Chung et al [37], Jani et al [38], and others. A comparison of the present paper with the relevant literature is provided in Table 1 to help the readers understand the contributions of our model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study endeavors to address this gap by making contributions to three streams of the literature: (1) carbon emission reduction policies, (2) advance sales and trade credit, and (3) the inventory model with price-dependent demand. EPQ V Tiwari et al [11] Production-inventory V Mishra et al [12] EPQ V Shen et al [13] Production-inventory V Cheng & Ouyang [22] EOQ V V V Cheng et al [25] EOQ V V Duary et al [26] EOQ V V V Li et al [35] EOQ V V Jani et al [38] EOQ…”
Section: Literature Reviewmentioning
confidence: 99%
“…A powerful strategy is to consider the dynamic cost function of demand, where the demand varies in response to client demand. These characteristics served as the impetus for the study, which found that a dynamic pricing technique is more effective at raising revenue than adopting a fixed sales price [6]. Even if they are making losses, companies that follow this price-cultivation strategy do not decrease their product pricing to boost sales because they view such losses as investments in price development.…”
Section: Introductionmentioning
confidence: 99%